Curcumin alleviates high-fat diet-induced hepatic steatosis and obesity in association with modulation of gut microbiota in mice. (May 2021) - Li, Shuo; You, Jinming; Wang, Zirui; Liu, Yue; Wang, Bo; Du, Min; Zou, Tiande
Graphical abstract: Highlights: Curcumin (Cur) alleviated hepatic steatosis and insulin resistance in obese mice. Cur increased abundance of Bacteroides, Parabacteroides, Alistipes and Alloprevotella . Cur increased the caecal and colonic short chain fatty acids (SCFA) contents. Cur reduced endotoxin-producing Desulfovibrio bacteria and circulating serum LPS. The dominant bacterial taxa altered by Cur were related with improvement of obesity. Abstract: Curcumin (Cur) is a natural polyphenol with beneficial effect against obesity and related metabolic disorders, but its precise mechanisms of action remain to be defined due to its limited systemic bioavailability. We hypothesized that gut microbiota may be a prospective therapeutic target for Cur-induced metabolic benefits. This study aimed to investigate whether the metabolic adaptations resulting from Cur supplementation were mediated by the gut microbiota in high-fat diet (HFD)-fed obese mice. C57BL/6 mice were fed a control diet or a HFD diet with or without 0.2% Cur for 10 weeks. Lipid profiles, insulin sensitivity, hepatic metabolism, gut microbiota composition and short-chain fatty acid (SCFA) production were determined. Dietary Cur reduced fat mass, hepatic steatosis and circulating lipopolysaccharide levels and improved the insulin sensitivity in HFD-fed mice. More importantly, Cur supplementation modulated the gut microbiota composition and ameliorated intestinal dysbiosis by decreasing the ratio of Firmicutes/Bacteroidetes and endotoxin-producing Desulfovibrio bacteria and increasing the abundance of Akkermansia population and SCFA-producing bacteria, such as Bacteroides, Parabacteroides, Alistipes and Alloprevotella, along with increases in caecal and colonic SCFA concentrations. These dominant bacterial genera altered by Cur showed strong correlations with the obesity-related metabolic parameters in HFD-fed mice. In conclusion, our data suggest that Cur alleviated metabolic features of hepatic steatosis and insulin resistance in HFD-fed obese mice, which might be associated with the modulation of gut microbiota composition and metabolites.